TRADISI TARI RONGGENG PASER DI KELURAHAN KUARO KABUPATEN PASER PADA TAHUN 2008-2025 - Maulida Rusdiana Zuhriah; Syaharuddin; Fitri Mardiani; Dewicca Fatma Nadilla (Historia, 2027)
Along with rapid globalization and modernization, the Ronggeng Paser Dance Tradition in the Village of Kuaro serves as an identity and adhesive force within society, but is starting to be marginalized by foreign cultures entering the region. The aim of this research is to describe the background of the Ronggeng Paser Dance in the Village of Kuaro and the development of the Ronggeng Paser Dance Tradition in the Village of Kuaro from 2008 to 2025. The method used is a historical method consisting of four stages: first, heuristics is carried out by collecting primary sources in the form of interviews with informants, documents, and documentation. Second, source criticism is applied in two steps: external criticism and internal criticism. Third, interpretation is carried out by interpreting and examining the historical facts of the Ronggeng Paser Dance Tradition in Kuaro Village. Fourth, historiography, namely the presentation of a chronological and analytical reconstruction of events in the form of scientific writing. This study reveals that Tari Ronggeng Paser represents a cultural acculturation between the indigenous Paser and Malay peoples, emerging during the Sadurengas Sultanate era. Since becoming part of the Kuaro Village administration, Ronggeng Paser Dance has undergone changes in its presentation, accessories, and cultural status. In conclusion, this traditional dance meaningfully represents the cultural identity of the Kuaro Village community.